2002
DOI: 10.1016/s0014-5793(02)03713-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the region of AT2 receptor needed for inhibition of the AT1 receptor‐mediated inositol 1,4,5‐triphosphate generation

Abstract: Increase in the intracellular inositol triphosphate (IP 3 ) levels in Xenopus oocytes in response to expression and activation of rat angiotensin II (Ang II) receptor AT1 was inhibited by co-expression of rat AT2 receptor. To identify which region of the AT2 was involved in this inhibition, ability of three AT2 mutants to abolish this inhibition was analyzed. Deletion of the C-terminus of the AT2 did not abolish this inhibition. Replacing Ile249 in the third intracellular loop (3rd ICL) of the AT2 with proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The intracellular third loop (ICL3) of the AT 2 receptor was shown to be important for its coupling to G i (Hayashida et al, 1996). Evidence of ICL3 involvement was also shown in AT 2 receptor induction of apoptotic responses in the PC12W neuronal lineage cells and in AT 2 receptor-mediated inhibition of IP 3 generation in Xenopus oocytes (Kumar et al, 2002). More recent studies implicated the involvement of G i in AT 2 receptor-dependent increases in nitric oxide synthase expression (Li et al, 2007a) and the inhibition of proximal tubule Na + -ATPase by Ang(1-7) Gohlke et al, 1998;Siragy, 2000).…”
Section: E Signalingmentioning
confidence: 87%
“…The intracellular third loop (ICL3) of the AT 2 receptor was shown to be important for its coupling to G i (Hayashida et al, 1996). Evidence of ICL3 involvement was also shown in AT 2 receptor induction of apoptotic responses in the PC12W neuronal lineage cells and in AT 2 receptor-mediated inhibition of IP 3 generation in Xenopus oocytes (Kumar et al, 2002). More recent studies implicated the involvement of G i in AT 2 receptor-dependent increases in nitric oxide synthase expression (Li et al, 2007a) and the inhibition of proximal tubule Na + -ATPase by Ang(1-7) Gohlke et al, 1998;Siragy, 2000).…”
Section: E Signalingmentioning
confidence: 87%
“…In the renal PT, ANG II binds to the AT 1 and interacts primarily with G q proteins, leading to activation of PKC and to mobilization of Ca 2ϩ from intracellular stores (13). X. laevis oocytes lack endogenous receptors for ANG II but have powerful G q protein-linked PKC and Ca 2ϩ signaling pathways that can be activated by agonists of recombinant mammalian receptors (2,10,18,23,36). Therefore, we heterologously coexpressed the human hkNBCe1 with the rat AT 1B receptor in X. laevis oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Activated AT2R induces a vasodilator cascade of BK/NO/cyclic guanosine monophosphate (cGMP), stimulates various protein phosphatases (SHP1, MKP1, and PP2A), and inhibits cell growth. We have shown that the AT2R exerts antagonistic effects on AT1R signaling, and this effect is mediated via the third intracellular loop of the AT2R [52]. We have also shown that the AT2R interacts with the ErbB family receptors and Na + /H + exchanger NHE6 via its third intracellular loop and C-terminal cytoplasmic domain [52,53].…”
Section: Ang II and Its Derivatives: The Paradigm Shift And The Vasodmentioning
confidence: 99%
“…We have shown that the AT2R exerts antagonistic effects on AT1R signaling, and this effect is mediated via the third intracellular loop of the AT2R [52]. We have also shown that the AT2R interacts with the ErbB family receptors and Na + /H + exchanger NHE6 via its third intracellular loop and C-terminal cytoplasmic domain [52,53]. The AT2R also interacts with a family of AT2R-interacting proteins involved in neuronal differentiation, vascular remodeling, and tumor suppression via its C-terminal domain [54].…”
Section: Ang II and Its Derivatives: The Paradigm Shift And The Vasodmentioning
confidence: 99%